Professional development shaping teacher agency and creative insubordination - Lopes,Celi Espasandin (2016)
Abstract The goal of this paper is to discuss the acts of creative insubordination of four mathematics teachers revealed in their narratives. The four teachers shared a common experience; they participated in a course entitled Teaching Mathematics in the Early Grades, which contributed to their professional development. Through the narratives, we identify how the course provoked teachers' agency and their acts of creative insubordination. The collaborative nature of the course, along with the reflection on practice, the group deliberations about implementing alternative teaching strategies, and the documentation of student learning, provided teachers with the confidence and self-efficacy necessary to defend the multiple dimensions of their practice and their acts of creative insubordination.